Versatility of Latissimus Dorsi Free Flap-a Prospective Study (Journal of Dhaka Medical College, 2021)
Introduction: Free flaps offer a great variable of available tissues to cover larger, multifocal or multistructural defects. The choice among different free flap is dependent upon their recipient site requirement. Reconstruction with latissimus dorsi flap is now versatile tool in coverage. It can resurface large wound with reliable vascularity, consistent anatomy ,long pedicle length, opportunity for tailoring of flap. It has less donor site morbidity and has very little post-operative complications.Objective: To evaluate the versatility of free Latissimus dorsi flap for soft tissue reconstruction.Materials and methods: A prospective, observational study design was used in Department of Plastic Surgery of Dhaka Medical College and Hospital. Here 20 patients with soft tissue defect of variable sizes over lower limb, head neck and trunk underwent coverage with microvascular surgery. The study was carried out from July 2017 to June 2018.Result: Regarding the age distribution, the mean age was 35.65with an SD of + 10.81. The lowest age was 20years and the highest age was 56 years, Male female ratio was 3:2.The major cause (65.0%) of soft tissue defect of the samples was RTA. The flap was used to reconstruct the soft tissue defect over lower leg in 13 (65%)cases, on scalp 05 (25%) cases and over anterior trunk in two cases. The mean flap dimension was 229.25cm2 and its range was between 120 – 384 cm2. The standard myocutaneous flap was harvested in 80% cases, chimeric (10%) and partial Latissimus muscle flap in two cases. The donor site in all the 20 (100%) cases was closed primarily. The outcome of reconstruction was excellent in 16(80%), good in 02 (10%) cases and poor in 02 (10%) cases. There was no significant complication during the three months postoperative period.Conclusion: The Latissimus dorsi flap is a versatile option for resurfacing the soft tissue defect in different areas of the body with variable flap components and with minimal donor site morbidity.J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 142-152